2015
DOI: 10.1016/j.addr.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel platform for cancer therapy using extracellular vesicles

Abstract: Extracellular vesicles (EVs) are nanometer-sized membranous vesicles and are involved in cell-to-cell communication. EVs contain several types of functional molecules, such as proteins, mRNAs, and microRNAs (miRNAs). Over the past several years, EVs have emerged as potential tools for a drug delivery system (DDS) that can target organs or cells. EVs have a function of organ tropism and are naturally occurring from cells. Therefore, EVs have expected as naturally DDSs, which have the organ tropism and a low sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 62 publications
0
68
0
1
Order By: Relevance
“…44 Over the past decade, thousands of researchers have contributed to the development of exosome-based vehicles for targeted delivery of therapeutics to diseased, including neurodegenerative diseases 4 and cancer. 48 Collectively, these studies have identified advantages of exosomes, over viruses and artificial nanoparticles, for the targeted delivery of therapeutics to diseased cells. However, the potential of engineered exosomes for clinical therapies is limited by their very challenging manufacture, and the need to conduct a comprehensive molecular and functional characterization on each preparation prior to a treatment, both of which are expensive and labor-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…44 Over the past decade, thousands of researchers have contributed to the development of exosome-based vehicles for targeted delivery of therapeutics to diseased, including neurodegenerative diseases 4 and cancer. 48 Collectively, these studies have identified advantages of exosomes, over viruses and artificial nanoparticles, for the targeted delivery of therapeutics to diseased cells. However, the potential of engineered exosomes for clinical therapies is limited by their very challenging manufacture, and the need to conduct a comprehensive molecular and functional characterization on each preparation prior to a treatment, both of which are expensive and labor-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, EVs have increasingly been under investigation as novel modulators for different therapeutic purposes, including anticancer strategies, vaccination, targeted drug delivery, immunomodulation, and tissue regeneration [22, 41, 42]. Therefore, several possible applications for EVs-mediated therapy have been proposed (Figure 1) [14, 43–49]. …”
Section: Cell-derived Vesiclesmentioning
confidence: 99%
“…In addition, exosomes have been considered as a novel platform for cancer therapy. 35 Through the untiring efforts of researchers, we speculate that exosomes may work as potent therapeutics in HSCR, as it can deliver drugs to selective targets. Certainly, more studies are needed to apply exosomes in a drug-delivery system.…”
Section: Discussionmentioning
confidence: 99%